LTE Network Structure, QoS Considerations, Bearers and Interfaces (International Journal of Engineering and Computer Science, 2017)
in this paper a comprehensive discussion about the entire EPS network structure and functionality of the various nodes residing  in both radio access part  and non radio network part is provided. The EPS interfaces, bearer establishment, QoS criteria and interworking with other networks such GSM also have outlined.